2002
DOI: 10.1063/1.1478157
|View full text |Cite
|
Sign up to set email alerts
|

High-power 400-nm-band AlGaInN-based laser diodes with low aspect ratio

Abstract: High-power blue-violet laser diodes with aspect ratio as low as 2.3 and threshold current down to 33 mA have been realized. The relationship between threshold current and optical confinement factor was investigated in order to minimize the beam divergence angle perpendicular to the junction plane (θ⊥). θ⊥ was found to decrease with reduction of the optical confinement factor, whereas threshold current density increased. A new layer structure, in which a p-typed cladding layer was located next to an AlGaN elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 8 publications
1
31
0
1
Order By: Relevance
“…The ridge depth was adjusted to yield a θ ʈ of 9°. A GaInN-interlayer was inserted as an optical guiding layer, contributing to an improvement in laser characteristics [11]. A 1.4-µm-wide ridge stripe was formed on the ELO wing regions, and this ridge stripe was covered with a stacked layer of Si on SiO 2 to obtain high kink-free output power [9].…”
mentioning
confidence: 99%
“…The ridge depth was adjusted to yield a θ ʈ of 9°. A GaInN-interlayer was inserted as an optical guiding layer, contributing to an improvement in laser characteristics [11]. A 1.4-µm-wide ridge stripe was formed on the ELO wing regions, and this ridge stripe was covered with a stacked layer of Si on SiO 2 to obtain high kink-free output power [9].…”
mentioning
confidence: 99%
“…However, AlGaN single EBL with high Al content induces strain in the active layer, degrading the emission efficiency of InGaN active layer. Asano et al reported that the InGaN interlayer can be inserted between the active layer and the AlGaN electron blocking layer to reduce this strain [7]. This high strain induced from AlGaN electron blocking layer is also one of the major factors to affect the poor properties of LD.…”
mentioning
confidence: 95%
“…In comparison to the Al x Ga 1Àx N buffer layers, the use of In x Ga 1Àx N waveguides could be difficult because their fabrication requires a low growth temperature which may limit the smoothness of the epitaxial surface. Nevertheless, laser-diodes whose waveguides contain In x Ga 1Àx N have recently been fabricated and their improved performance was demonstrated [8,9].…”
mentioning
confidence: 99%